ANALISIS KEPUASAN PENGGUNA E-LEARNING SEBAGAI PENDUKUNG AKTIVITAS PEMBELAJARAN MENGGUNAKAN METODE EUCS - Apris Robi Darwi; Efrizon Efrizon (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
In this research to make the improvement of convenience that would later give also the satisfaction of any user that has used and be active in e-learning information systems which have been applied in engineering Electronics ft unp. This research using the method of end user computing satisfaction that in short EUCS are used to measure the level of user satisfaction with knowing the contribution factors of content, accuracy, shape, ease of usage and timeliness to be thorough by the author to apply to the scope of the Department of electronics engineering ft unp. This research using quantitative research, then conducted a descriptive analysis, inductive analysis, multiple regression and hypothesis testing. The results of the analysis of the data indicates that the variable in the method of EUCS jointly contribute the same significance of 45% to the satisfaction of users of the e-learning information systems in the Department of electronics engineering achievements in the unp ft. from research that has been done, is expected to be contributed to the Administration's e-learnngi in order to improve the quality of e-learning on the campus of the State University of padang in General and in the Electrical Engineering Universitas Negeri Padang in particular. Keywords: information systems, End User Computing Satisfaction, E-learning.